When FIFA Rules the World: Hegemoni FIFA Terhadap Indonesia Dalam Kasus Pembekuan PSSI 2015-2016 - Arry Bainus; Rusadi Kantaprawira; Indra Kusumawardhana (Andalas Journal of International Studies (AJIS), 2018)
The bitter sanctions against the Indonesian Football Association (PSSI) by the Fédération Internationale de Football Association (FIFA) in 2015-2016 revealed an irritate reality regarding how weak the position of the state is; when dealing with organizations that are considered as representations of global institutions in the world of football. Therefore, Indonesia's powerlessness has made the question why the state is powerless before FIFA as an international organization finds its importance. Using the Coxian approach to understand the World Orders, this article argues that this condition due to the FIFA’s hegemony which supported by three main aspects, namely; first, the idea of football which is a populist sport, must be separated from the political intervention of state power. Second, FIFA's material capacity has made football as a sport with high economic value, even in Indonesia itself. Finally, supported by the previous two aspects, the governance of FIFA institutions has gripped various regions of the world, so that it has created sovereignty in the world of football. Using critical analysis, the intellectual work of this paper does not only intend to improvise in the selection of topics but also presents alternative narratives in the contemporary constellation of contemporary international relations studies.